ACTIVE SHARING KNOWLEDGE UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN GURU- GURU MATEMATIKA SMA/SMK BINAAN MELALUI PENDAMPINGAN DI KULON PROGO - Giyarsih Giyarsih (JIPM (Jurnal Ilmiah Pendidikan Matematika), 2016)
This research is meant to explain the problem solving efford which is found in academic supervision toward teachers of Mathematics in some guided schools, explains the problem solving steps by the supervisor in guided schools, and shows the teaching quality improvement by the Mathematics teachers in those guded schools. This research was done to some guded schools where ten Mathematics teachers of Senior High Schools or Vocational High School in Kulon Progo District are the subject. The strategy for improving the quality of Mathematics teaching application is through treatment of companion teaching in active sharing knowledge for instance through planning, the step of treatment in the teaching, teaching procedures and class management. The result of acompaniying the teachers of Mathematics shows that Mathematics teachers in Kulon Progo Distric still need some guidance from the supervisors especially in term of innovative teaching process, where most teachers lack of motivation, the Active Sharing Knowledge method can improve the activism of the teachers through out the whole teaching activities, improve the quality of teaching process, students’ activism, concept mastery and teacher’s skills in teaching process as can be seen as followed: the teaching quality of Mathematics teachers using Active Sharing Knowledge is 5%, student’s participations is 46%, while teachers’ mastery of the concept is 14%, and positive reflection as a result of Mathematics Teachers guided teaching implementation using Active Sharing Knowledge where 84% stated agree and totally agree.